A Better and Faster end-to-end Model for Streaming ASR - Li, Bo; Gulati, Anmol; Yu, Jiahui; Sainath, Tara N.; Chiu, Chung-Cheng; Narayanan, Arun; Chang, Shuo-Yiin; Pang, Ruoming; He, Yanzhang; Qin, James; Han, Wei; Liang, Qiao; et al. (Proceedings of the ... IEEE International Conference on Acoustics, Speech and Signal Processing (1998), 2021)
End-to-end (E2E) models have shown to outperform state-of-the-art conventional models for streaming speech recognition [1] across many dimensions, including quality (as measured by word error rate (WER)) and endpointer latency [2]. However, the model still tends to delay the predictions towards the end and thus has much higher partial latency compared to a conventional ASR model. To address this issue, we look at encouraging the E2E model to emit words early, through an algorithm called FastEmit [3]. Naturally, improving on latency results in a quality degradation. To address this, we explore replacing the LSTM layers in the encoder of our E2E model with Conformer layers [4], which has shown good improvements for ASR. Secondly, we also explore running a 2nd-pass beam search to improve quality. In order to ensure the 2nd-pass completes quickly, we explore non-causal Conformer layers that feed into the same 1st-pass RNN-T decoder, an algorithm called Cascaded Encoders [5]. Overall, the Conformer RNN-T with Cascaded Encoders offers a better quality and latency tradeoff for streaming ASR.